Ranunculus tengchongensis and R. yanshanensis (Ranunculaceae), both described from Yunnan in China, are merged with R. trigonus - Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Ranunculus tengchongensis and R. yanshanensis (Ranunculaceae), both described from Yunnan in China, are conspecific with R. trigonus, a species distributed in southwestern China, particularly common in Yunnan province, and somewhat variable with respect to stem indumentum, shape and division of basal leaves, and length of their petioles. We therefore reduce R. tengchongensis and R. yanshanensis to the synonymy of R. trigonus herein.